Design and synthesis of mechanochromic poly(ether-ester-urethane) elastomer with high toughness and resilience mediated by crystalline domains. Issue 15 (25th March 2022) - Wang, Wenwen; Li, Manli; Zhou, Pengcheng; Yan, Zhong; Wang, Dong
Abstract : Poly(ether-ester-urethane) elastomers with spiropyran were designed and synthesized to perform mechanochromic behavior. Poly(ether-ester) precursor with crystalline PBT domains and PTMG soft segments endows it with high toughness and resilience. Abstract : Mechanochromic elastomers play an important role in stain sensing, materials damage alarm, stress detecting, etc . Low activation strain and stress, high toughness and resilience, and self-recovery are the essential properties needed to make mechanochromic elastomers useful in practical applications. In the present work we show the molecular design and synthesis of a polymer system to perform mechanochromic behavior by incorporating a spiropyran mechanophore molecule onto the linear backbone of thermoplastic poly(ether-ester-urethane) elastomer. The poly(ether-ester) precursor consists of crystalline poly(butylene terephthalate) hard segments and amorphous poly (tetramethylene glycol) soft segments, thus endowing the material with superior elasticity and high toughness. The toughness of the mechanochromic elastomer can reach up to ∼300 MJ m −3 and, meanwhile, the residual strain is below 23% under 200% strain after ten stretching cycles. We found that the newly designed elastomers, adopting crystallinity domains and amorphous domains, can regulate the mechanochromic activation energy by varying the content and molecular weight of soft segments and so achieve the lowest onset of color activation strain ( ε MC ) at ∼158%. Furthermore, cyclic tensile tests demonstrated that the elastomer could be utilized cyclically at least ten times with the same mechanochromic properties and resilience.